Qualitative evaluation of paediatric surgical otolaryngology content on YouTube. Issue 2 (13th February 2020) - Ward, B; Bavier, R; Warren, C; Yan, J; Paskhover, B
Abstract: Objective: This study evaluated the quality of YouTube content focusing on common paediatric otolaryngology procedures, as this content can influence the opinions and medical decisions of patients. Methods: A total of 120 YouTube videos were compiled to review using the terms 'adenoid removal', 'adenoidectomy', 'ear tubes', 'tympanostomy', 'tonsil removal' and 'tonsillectomy'. The Discern criteria was used to rate the quality of health information presented in each video. Results: The mean bias Discern score was 3.18 and the mean overall Discern score was 2.39. Videos including US board certified physicians were rated significantly higher ( p < 0.001) than videos without (bias Discern score = 3.00 vs 2.38; overall Discern score = 3.79 vs 1.55). The videos had been viewed a total of 176 769 549 times. Conclusion: Unbiased, high quality videos on YouTube are lacking. As patients may rely on this information when making medical decisions, it is important that practitioners continually evaluate and improve this video content. Otolaryngologists should be prepared to discuss YouTube content with patients.